Perceived fear and exercise difficulty in patients with migraine and their association with psychosocial factors: a cross-sectional study - Álvaro Reina-Varona; Beatriz Madroñero-Miguel; Alba Paris-Alemany; Roy La Touche (PeerJ)
Purpose Although pharmacological treatments for migraine have advanced, non-pharmacological approaches, such as exercise, offer additional benefits. However, many patients avoid physical activity due to fear of symptom exacerbation. This study aims to identify the most threatening and difficult exercises for patients with migraine and examine the relationship between exercise perceptions and factors such as physical activity levels, kinesiophobia, catastrophizing, and self-efficacy. Methods This cross-sectional study explored the perceived fear and difficulty of nine exercises shown via video demonstrations, and their association with psychological variables in patients with migraine. Participants aged 18–65 with physician-diagnosed migraines completed self-report measures of physical activity, kinesiophobia, catastrophizing, fear-avoidance beliefs, headache impact, neck disability, and self-efficacy. Results A total of 110 patients with migraine participated (88% women), with a mean age of 36 years. Chronic migraine was reported by 53% of participants. Significant differences in perceived fear and difficulty were observed across the nine exercises (p < 0.001), with jumping and spine extension rated as the most fear-inducing and difficult exercises, respectively. Beta regression models showed that the physical activity level, measured by the short form of the International Physical Activity Questionnaire (IPAQ-SF), was negatively associated with fear of jumping and difficulty of spine extension, whereas fear-avoidance beliefs were positively associated with both. A correlation analysis revealed a moderately significant negative association between the IPAQ-SF score and perceived fear of running. Conclusion Jumping, running, and spine extension were perceived as the most aversive exercises. Perceived fear and difficulty levels were associated with physical activity levels and fear avoidance beliefs, emphasizing the need to assess these factors before implementing therapeutic exercise interventions.